Pyomyositis presenting as myonecrosis secondary to methicillin-resistant Staphylococcus aureus bacteremia in chronic lymphocytic leukemia. Issue 5 (15th September 2022) - Coombs, Shannon; Bui, Albert; Mirzan, Haares S.; Robelin, Kimberly; Garner, Hillary W.; Krishna, Murli; Cowart, Jennifer B.
AABSTRACT: The incidence of pyomyositis in immunocompromised patients with HIV, diabetes, myelodysplastic syndromes, and acute lymphocytic leukemia is well documented. However, there are only a few reports of pyomyositis and myonecrosis in patients with chronic lymphocytic leukemia (CLL). We present a rare case of pyomyositis presenting as myonecrosis secondary to methicillin-resistant Staphylococcus aur eus bacteremia in a 72-year-old patient with CLL. Pyomyositis, although rare, warrants increased provider awareness and management, especially among CLL patients who pose diagnostic and treatment challenges.